1981
DOI: 10.1017/s0081305200027230
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Effects of the Food Stamp Program on Participating Households' Purchases: An Empirical Application

Abstract: The present legal authority for the Food Stamp Program (FSP) is the Food and Agriculture Act of 1977. As adopted, the legislation includes a thorough overhaul of the FSP enacted into law in 1964. The FSP provides direct subsidies in the form of additional food dollars to low-income households to enhance the purchasing of nutritionally adequate diets. The most significant effect both on participating households and the food industry is the elimination of the purchase requirement whereby participants pay for foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The conditional elasticities represent the change in the insurance premium occurring from responses of participating producers. The difference between the total and conditional elasticities results from changes in the participation in the insurance programs (Huang, Fletcher and Raunikar 1981). For example, given a 1 per cent increase in expected wheat yields, the crop insurance premium would decrease by 3.702 per cent.…”
Section: The Tobit Coefficients Inmentioning
confidence: 99%
“…The conditional elasticities represent the change in the insurance premium occurring from responses of participating producers. The difference between the total and conditional elasticities results from changes in the participation in the insurance programs (Huang, Fletcher and Raunikar 1981). For example, given a 1 per cent increase in expected wheat yields, the crop insurance premium would decrease by 3.702 per cent.…”
Section: The Tobit Coefficients Inmentioning
confidence: 99%
“…However, information on children’s intake is lacking in evaluations of food subsidy programmes [ 5 , 31 ]. The few economic studies that exist report findings from the US and have mixed results; while three studies reported that food vouchers were associated with increases in spending on fruit and/or vegetables [ 33 - 35 ], one showed a negative relationship [ 36 ] and two had mixed results or no association [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…A household access to food depends on a number of factors including food prices, household income and assets, etc. An increase in household income can improve their food security through access to food (Huang, Fletcher & Raunikar ,1981). Moreover, poor communities are very sensitive and vulnerable to shocks, i.e.…”
Section: Introductionmentioning
confidence: 99%